Tingkat Pengetahuan Remaja Tentang Perilaku Seks Bebas Di SMP Muhamadiyah 4 Daruba, Kabupaten Morotai, Maluku Utara - Mughni Wahdaniyah S; Asrida A; Hartati S; Jumriani Jumriani (Universitas Katolik Widya Karya Malang, 2023)
Adolescence is a critical and vulnerable period. In adolescents personality and individual character begins to form. One of the stages of adolescence is late adolescence which experiences many changes such as interest in the opposite sex, falling in love, and the development of reproductive organs. Interest in getting to know each other is natural, but if it crosses a line, such as having premarital sex, it is very contrary to the religion and culture of the Indonesian people. Free sex is sexual relations outside of marriage, which is still a serious problem for today's youth. research to describe adolescents' knowledge about free sex at the Muhamadiyah Morotai Middle School, Morotai Regency with respondents from the Muhamadiyah Morotai Middle School students in 2020. Research method, this research is a descriptive study with a cross-sectional approach to describe adolescents' knowledge about free sex. In conclusion, this study concluded that respondents with good knowledge were 75% with correct answers or good knowledge and 25% had sufficient and insufficient knowledge. Suggestions, it is suggested to schools to conduct more health education to students about free sex behavior to avoid the impact of infectious diseases and other reproductive health problems